2007
DOI: 10.1021/ol7023136
|View full text |Cite
|
Sign up to set email alerts
|

Steric Inhibition of π-Stacking:  1,3,6,8-Tetraarylpyrenes as Efficient Blue Emitters in Organic Light Emitting Diodes (OLEDs)

Abstract: The sterically congested tetraarylpyrenes 1-3, which can be readily accessed by Suzuki coupling, exhibit no-aggregation (pi-stacking) behavior in both solution and solid states. The indisposed tendency of 1-3 toward crystallization and their moderate molecular dimensions permit exploitation as blue light emitting materials in OLEDs with respectable device performances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
110
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(118 citation statements)
references
References 39 publications
6
110
0
Order By: Relevance
“…Recently, this problem is mainly solved by both the introduction of long or big branched side chains into pyrene molecules and co-polymerization with a suitable bulky co-monomer. Very recently, it was reported that pyrene derivatives are useful in OLEDs applications (Otsubo et al, 2002;Thomas et al, 2005;Ohshita et al, 2003;Jia et al, 2004;Moorthy et al, 2007) as hole-transporting materials (Thomas et al, 2005; or host blue-emitting materials (Otsubo et al, 2002;Ohshita et al, 2003;Jia et al, 2004;Moorthy et al, 2007). To date, various pyrene-based light-emitting materials have been disclosed in recent literatures, which can be roughly categorized into three types of materials: (1) Functionalized pyrene-based light-emitting monomers; (2) Functionalized pyrene-based lightemitting dendrimers; and (3) Functionalized pyrene-based light-emitting oligomers and polymers.…”
Section: Pyrene and Pyrene Derivativesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, this problem is mainly solved by both the introduction of long or big branched side chains into pyrene molecules and co-polymerization with a suitable bulky co-monomer. Very recently, it was reported that pyrene derivatives are useful in OLEDs applications (Otsubo et al, 2002;Thomas et al, 2005;Ohshita et al, 2003;Jia et al, 2004;Moorthy et al, 2007) as hole-transporting materials (Thomas et al, 2005; or host blue-emitting materials (Otsubo et al, 2002;Ohshita et al, 2003;Jia et al, 2004;Moorthy et al, 2007). To date, various pyrene-based light-emitting materials have been disclosed in recent literatures, which can be roughly categorized into three types of materials: (1) Functionalized pyrene-based light-emitting monomers; (2) Functionalized pyrene-based lightemitting dendrimers; and (3) Functionalized pyrene-based light-emitting oligomers and polymers.…”
Section: Pyrene and Pyrene Derivativesmentioning
confidence: 99%
“…Quite recently, several 1,3,6,8-tetraaryl-functionlized pyrenes as efficient emitters in organic light emitting diodes (OLEDs) have been reported. Moorthy et al (Moorthy et al, 2007) prepared three sterically congested tetraarylpyrenes 16-18, which can be readily accessed by Suzuki coupling between the 1,3,6,8-tetrabromopyrene (2e) and the corresponding arylboronic acids in isolated yields. The UV-vis absorption spectra of these arylpyrenes revealed a vibronic feature that is characteristics of unsubstituted parent pyrene with short wavelength absorption maximum at ca.…”
mentioning
confidence: 99%
“…19 Various successful procedures have been developed in the last few years to frustrate the ACQ process. These include (a) distorted/twisted luminophores; [20][21][22] (b) long aliphatic chain substitution of the core luminophore; [23][24][25] (c) spiro compounds; [26][27][28] (d) insertion of bulky substituents to the core luminophore [29][30][31] and (e) a dipole stacking model. 32 All these approaches make the luminophore highly emissive in the solid state because of prevention of aggregation quenching at a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Its photophysical properties [1 -5] and its supramolecular chemistry [4 -9] have been widely studied. Structural modifications [10] allow for many applications, which include the development of fluorescent dyes [11], molecular electronics [2,12], optical sensors [13], fieldeffect transistors [13] and photovoltaic cells [14,15]. A wide range of fabrication techniques in combination with modern synthetic methods allow for the development of new materials which meet special demands and applications.…”
Section: Introductionmentioning
confidence: 99%